(untitled) (Research, Society and Development, 2024)
Introduction: Syphilis, one of the leading sexually transmitted infections, represents a growing public health concern, especially in Sergipe, which became the second-highest state in the Northeast in reported cases between 2019-2020, behind only Bahia. Early detection and proper treatment are essential to prevent disease progression and complications. The objective of this article is to present an analysis of acquired syphilis detection in Sergipe over the past ten years. This type of study is crucial to identify trends, inform public health policies, and raise awareness, assisting in disease control. Methodology: An observational study was conducted based on data analysis from the TABNET system on the DATASUS portal (Ministry of Health), considering all municipalities in the state of Sergipe between 2013 and 2023. Reported cases of acquired syphilis (ICD-10 A51, A52, and A53) during the period were analyzed. Results: A total of 11,664 cases of acquired syphilis were recorded, with incidence rates ranging from 4.95% to 18.04%. A decline was observed until 2019, followed by a rapid increase, with incidence tripling during the period. Aracaju, the capital, reported the highest number of cases (26.29%). Gender distribution was similar, and the 20-39 age group was the most affected (58.99%), with a predominance of individuals of mixed race (69.77%). In terms of education, the highest prevalence was observed among people with 5th to 8th-grade education (17.33%), followed by those with complete high school education (15.20%). Finally, 44.48% of cases evolved to clinical cure, with mortality reported in less than 1% of cases.